Comparison of perioperative hidden blood loss for intertrochanteric fractures in the elderly by different intramedullary fixations: A randomized controlled study protocol. Issue 48 (25th November 2020) - Zheng, Huayong; Zhang, Yang; Wang, Hao; Sun, Tiansheng; Sun, Qicai
Abstract: Background: Till date only a few studies have reported the clinical outcomes of intraoperative hidden blood loss of intertrochanteric fracture in the old people treated with various intramedullary immobilizations. The aim of the trial is to investigate the best choice for treating intertrochanteric fractures, as well as the hidden blood loss among different intramedullary fixations. Methods: This randomized, single-blind, superiority clinical trial was admitted by the Ethics Committee in our hospital (The 7th Medical Center of PLA, 20200602DM). The eligibility criteria were: Over 60 years or older; Fresh closed intertrochanteric fractures (AO 31-A2); A low- intensity trauma; With complete records of serial full blood count, including haematocrit value on admission and 72 hour after surgery. Patients who met any of the following conditions would not be able to participate in the test: composite femoral fracture, under 65 years of ages, experience of femoral fractures, surgical contraindications, nonambulatory before the presenting injury, or presence of any other traumatic fractures. 120 participants with unstable intertrochanteric fractures, treated by Gammar nail, (n = 40), Proximal Femoral Nail Antirotation (n = 40) and Intertrochanteric Antegrade Nail (n = 40) instruments were enrolled in this research. The main outcome measures were total blood loss and hidden blood loss, which were evaluated based on the haematocrit change after the operation. The experimental data was analyzed and sorted out with SPSS program (ver.19; SPSS Inc., Chicago, IL). Results: This experiment had strict inclusive criteria and exclusive criteria and a well- regulated intervention. Conclusions: The results of this trial will provide more evidence on which technique can better treat unstable intertrochanteric fracture. Trial registration: This study protocol was registered in Research Registry (researchregistry5788).